Family Economy and Its Implementation on Compulsory Education Program - Hendaryati, Neni (Fakultas Ekonomi, Universitas Negeri Semarang, 2015)
This research aims to determine and describe family economy and the implementation of nine-year compulsory education program at Kajenengan village, Bojong Sub District of Tegal in 2014. It was a qualitative descriptive study. The population of study was 1011 family leaders. This research used purposive sampling technique and 252 family leaders or about 25% of the population were as samples. Data were collected by observation, interview and documentation. Then, the data was analyzed by using data reduction, data display, and concluding. Findings show that the obstacles of social and economy faced by family: 47.20% of Kajenengan villagers are as farm labors, 28,57 % of Â villagers get the average income per day from IDR 21,000 up to IDR 30,000, Â 33.73% of them have 5-6 family members in their nuclear family, and 32.80% of them who prioritize in education, especially on nine-years compulsory education program. Â Then, there are only 8.73% of samples who implement the nine-year compulsory education program. Moreover, 47.62% family leaders say that most of their family members join the nine-year compulsory education and 43.65% of the family leaders say that all of their family members do not join the nine-year compulsory education at all.